Research on the thermal performance of wall insulation materials and their impact on energy consumption in nearly zero-energy buildings - Jun Xu; Yukun Zhu; Yu Gao; Rongshui Qin (PLoS ONE, 2026)
This study explores the thermal performance of wall insulation materials and their impact on the energy consumption of nearly zero energy buildings (NZEBs) in the hot summer and cold winter climate zone of central and southern Anhui Province, China. A bidirectional environmental chamber was constructed at university to evaluate two graphite-enhanced insulation materials—graphite extruded polystyrene (XPS, extruded polystyrene board; GXPS, graphite extruded polystyrene board) and graphite expanded polystyrene (SEPS, graphite molded polystyrene board)—under simulated seasonal temperature and humidity conditions. Experimental results show that GXPS exhibits superior thermal insulation performance during winter and transitional seasons, with a thermal conductivity as low as 0.023 W/(m⋅K) and stable surface heat flux under large temperature differentials. In contrast, SEPS performs notably well in hot and humid summer conditions, featuring uniform internal temperature distribution and pronounced thermal inertia, which effectively delays heat transfer. Dynamic thermal response analysis reveals that GXPS has a fast cooling response suited for winter, while SEPS demonstrates delayed heating behavior that mitigates summer heat stress. Building energy simulation results indicate that a GXPS insulation thickness of 50 mm achieves optimal energy savings in the region, with annual energy reduction rates between 13.6% and 22.0%. The complementary thermal properties of GXPS and SEPS provide a promising envelope design strategy for regional NZEBs, contributing to energy efficiency improvement and supporting China’s carbon neutrality targets.